OPTIMASI FORMULA SIRUP EKSTRAK TERSTANDAR DAUN KEMBANG SEPATU (Hibiscus rosa-sinensis L.) DENGAN KOMBINASI SORBITOL, XANTHAN GUM, DAN GLISERIN MENGGUNAKAN D-OPTIMAL MIXTURE DESIGN - , ANDI NAFISAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ethanolic extract of the leaves of hibiscus (Hibiscus rosa-sinensis L.) has been reported to have mucolytic activity in vitro. To improve the aesthetics and acceptability extract, it is necessary to be formulated into a suitable dosage syrup. Ethanolic hibiscus leaf extract concentration used in syrup is 0.75%. Syrup is made by optimizing the levels of sorbitol, xanthan gum and glycerinuse method D-Optimal Mixture Design. Evaluation based on physical properties syrup syrup syrup include viscosity, ease of pouring, the degree of acidity (pH), and perceptic taste. To determine the difference between the optimum formula prediction software results with optimum physical properties formulas experimental results continued by by one-sample t-test with 95% of confidence level. Mucolitic activity test of optimal syrup was compared with 0.1% acetylcysteine syrup (positive control). Total phenolic content of the ethanolic extract of leaves of the hibiscus flower is 0.504 Â± 0.004 % and total flavonoid content in the extract was 0.289 Â± 0.0198 %. Desirability value of D-Optimal Mixture Design is 0.84 with optimum proportion of the excipients are in the 15.53 %, of glycerin